Perencanaan Perawatan Mesin Serut Dengan Metode Reliability Centered Maintenance (RCM) Di CV. Andri Mebel Serang - Rahmatullah, Asep; Budiharjo, Budiharjo; Wahyudi, Diki (STTI Bontang, 2022)
One of the production factors that must be optimized for its use is the production machine. The machine used in production activities must be able to operate optimally, operation is said to be optimal if the downteme value is minimum. To ensure optimal engine operation, a proper machine maintenance system is needed. One of the problems faced by CV. Andri Mabel Serang is a shaving machine malfunction that eventually hampers the production process. The purpose of this study is to reduce downtime and find out the maintenance system and maintenance policy in reducing maintenance costs on the machine. The analysis used in this study is to use reliability analysis and for its completion using the RCM (Reliability Centered Maintenance) method. The results of calculations from reliability are known to an average of 87% which means machine maintenance in cv. Andri Mabel Serang is still below the world standard class (≥90%). From the RCM analysis, it is known that the maintenance cost is Rp. 116,447. Meanwhile, the corrective fee is as low as Rp. 590,000. Based on the smallest value of the RCM analysis, the company should carry out shaving machine maintenance every 5 months. After filling in the FMEA worksheet table of one of the components of the shaver machine, it can be found that the machine that was damaged was the shaver. The component of the drawstring machine that was damaged was the eyelet component. This component functions as a wood scraper